Live Streaming Introduction and Mode Selection: Strategic Analysis and Optimal Decision-Making for a BOPS Retailer - Shuai Feng; Wanling Zhou; Jiqiong Liu (IEEE Access, 2025)
In the context of e-commerce live streaming, this paper considers the issue of BOPS (buy online, pick up in store) retailers intending to introduce live streaming sales to provide greater shopping flexibility and cater to consumers’ diversified shopping preferences. We classify consumers into online and offline groups on the basis of their lifestyles and shopping habits. As consumer shopping behavior becomes increasingly diversified, the BOPS model enhances shopping flexibility by integrating online and offline resources, whereas live streaming sales, with their real-time interaction and product display capabilities, emerge as a key driver of retail innovation. However, existing studies have often analyzed BOPS or live streaming sales in isolation, lacking a systematic examination of their synergistic effects. To address this gap, this paper constructs a three-stage strategic model that integrates BOPS and live streaming sales (N strategy: not introducing live streaming sales; S strategy: adopting the merchant self-broadcasting mode; I strategy: adopting the influencer cooperation live streaming mode) and analyzes profits under different strategies through utility theory, game theory, and numerical simulation. The study reveals that, first, the introduction of live streaming sales by BOPS retailers leads to higher product prices, with even higher prices set when collaborating with influencers for live streaming. Second, the self-broadcasting model typically significantly increases market demand for BOPS retailers, whereas whether collaboration with influencers for live streaming results in demand growth depends on the extent to which the positive effects of live streaming services enhance consumers’ perceived value. Finally, BOPS retailers can benefit from introducing live streaming sales channels, but the choice of live streaming model is influenced by the fixed fee charged by influencer hosts. A high fixed fee ( $T\gt 0.25$ ) prompts BOPS retailers to prefer the self-broadcasting model, whereas a low fixed fee ( $T\lt 0.2$ ) makes collaboration with influencers for live streaming a win-win choice for both BOPS retailers and influencers. The results of the numerical research and theoretical analyses are consistent, further indicating that BOPS retailers can profit from the introduction of a live streaming sales channel. This study, which is based on utility theory, clearly delineates three strategic decision-making models for BOPS retailers when choosing live streaming methods, and it provides corresponding rules for strategy option selection, offering theoretical support for BOPS retailers.